Styryl pyranones with apoptosis activities from the sporocarps of Phellinus igniarius. (August 2021) - Cao, Yinglong; Liu, Yi; Wang, Ge; Wang, Wenqiong; Li, Yougui; Xuan, Lijiang
Graphical abstract: Highlights: Chemical constituents of the sporocarps of Phellinus igniarius were isolated and identified. Three novel styryl pyranones were reported in this paper. Compound 4 and 10 can increase Hela-/- cell death via activating apoptosis pathway other than necroptosis. Abstract: Three previously unreported compounds, phelliigniarin A (1 ), phelliigniarin B (2 ), phelliigniarin C (3 ), and seven known compounds were isolated and identified from the sporocarps of Phellinus igniarius . These structures were elucidated on the basis of spectroscopic analysis. Compound 4 and 10 triggered apoptosis of Hela-/- cell at the dose of 20 μM.